Pengaruh Citra Merek dan Online Customer Review terhadap Minat Beli Konsumen pada Marketplace Shopee (Studi pada Pengguna Shopee di Banjarmasin) - Eka Ratnasari; Rizki Muslim Hidayat; M. Hasanur Arifin; Humaidi (Business Administration, FISIP ULM, 2022)
ABSTRACT : This study aims to determine and examine the effect of partially and simultaneously Brand Image and Online Customer Review on Consumer Purchase Intentions on the marketplace Shopee in Banjarmasin. This study uses a quantitative approach with the determination of the sample using purposive sampling technique. The respondents in this study amounted to 135 people who live in the city of Banjarmasin, have the Shopee application and have shopped online at the marketplace Shopee. The data collection technique uses a questionnaire that has been tested for validity and reliability, distributed directly and with the help of a google form link. The scoring technique uses ascale Likert. The analytical method used is Multiple Linear Regression using the SPSS Version 26 application. The results of the study prove based on a partial test (t test) that the Brand Image variable (X1) has a significant effect on Consumer Purchase Intentions (Y) with a significant value of 0.000 < 0, 05 and the t-count value is 8.404 > t table 1.9781 and the variable Online Customer Review (X2) has a significant effect on Consumer Purchase Intentions (Y) with a significant value of 0.000 <0.05 and t-count 5.370 > t table 1.9781. The results of the simultaneous test (F test) of Brand Image (X1) and Online Customer Review (X2) have a significant effect on Consumer Purchase Intentions (Y) with a significant value of 0.000 <0.05 and F count 128.712 > F table 3.06 Keywords: Brand Image, Online Customer Review, Purchase Intention